Hubungan Tingkat Pengetahuan, ASI Eksklusif dengan Kejadian Stunting pada Balita Usia 12-59 Bulan di Wilayah Kerja Puskesmas Tarusan Kabupaten Pesisir Selatan - Erni Maywita; Rika Amran (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2022)
The prevalence of stunting in West Sumatra in 2018 was 20.3%. Based on the West Sumatra Riskesdas report, the prevalence of stunting in South Pesisir Regency in 2018 was 19.73%. Tarusan Health Centre is one of the areas that contributes to the stunting prevalence rate. Based on the recap of monitoring nutritional status at the Tarusan Community Health Centre in February 2021, it was found that the prevalence of stunting was 8.9%. This study aims to determine the relationship between knowledge and exclusive breastfeeding with the incidence of stunting in toddlers aged 12 - 59 months in the Tarusan Health Centre Working Area in 2021. This type of research is analytical using a casecontrol design. This research was conducted in 2021 in the Tarusan Health Centre Working Area. The population in this study were mothers who had toddlers aged 12 - 59 months. Sample determination was carried out using the formula Paired case control study by classifying the case group and control group taken based on a 1:1 ratio with the results of the calculation of 130 cases and 130 controls. Sampling was carried out using proportional random sampling technique. Primary data collection was carried out using interview techniques using questionnaires. Data analysis included univariate and bivariate analysis to test the significant relationship between the level of maternal knowledge, exclusive breastfeeding, and the incidence of stunting in the Tarusan Health Centre Working Area using the chi square test at the 95% confidence level (p < 0.05). The results of the study 27.3% of toddlers were not exclusively breastfed. 20.8% of mothers of toddlers have low knowledge about nutrition. There was a significant association of breastfeeding (p = 0.26, OR value 1.9 (CI 95%)) and knowledge (p value = 0.047, OR value = 4.6) with the incidence of stunting. There is a relationship between exclusive breastfeeding, knowledge and the incidence of stunting in toddlers aged 12 - 59 months in the Taruran Health Centre working area in 2021, it is hoped that health workers can provide education and further encourage mothers to want to breastfeed their toddlers exclusively.